Pelatihan Online Basic PHP Programming untuk Aparatur Sipil Negara (ASN) dan Non ASN Pemerintah Kota Bekasi - Syahbaniar Rofiah; Rita Wahyuni Arifin; Rully Pramudita; Ari Nurul Alfian; Didik Setiyadi (Sekolah Tinggi Teknik - PLN, 2020)
Technology currently plays an important role in the Government sector, with the existence of this technology each sector can maximize its system. State Civil Apparatuses (ASN) and Non-ASN Government in mastering basic PHP programming is very much needed. Implementation of Community Service (PkM) is carried out in accordance with the form of the implementation of the MoU that has been carried out between Bekasi City Government and Bina Insani University. The training was conducted online through a meeting zoom which was attended by 88 participants with the overall results of the training giving a positive response in the range of grades 4 (Good / Satisfied / Good) and 5 (Very Good / Very Satisfied / Very Good).